Network analysis of anxiety and depressive symptoms among patients with heart failure - Qiuge Zhao; Xiaofei Sun; Yanting Zhang; Yuzhen Zhang; Cancan Chen (BMC Psychiatry)
Abstract Background Anxiety and depressive symptoms are common among patients with heart failure (HF). Physical limitations, lifestyle changes, and uncertainties related to HF can result in the development or exacerbating of anxiety and depressive symptoms. However, the central and bridge symptoms of anxiety and depressive symptoms network among patients with HF remain unclear. Network analysis is a statistical method that can discover and visualize complex relationships between multiple variables. This study aimed to establish a network of anxiety and depressive symptoms and identify the central and bridge symptoms in this network among patients with HF. Methods This study employed a cross-sectional study design and convenience sampling to recruit patients with HF. This study followed the Helsinki Declaration and was approved by the Research Ethics Committee of Hospital. The Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire (PHQ-9) were administered to evaluate anxiety and depressive symptoms among patients with HF, respectively. Network analysis of anxiety and depressive symptoms was performed using R. Results In the anxiety and depressive symptoms network, PHQ2 (feeling down, depressed, or hopeless), PHQ7 (inability to concentrate), and GAD4 (difficulty relaxing) were the most central symptoms. Anxiety and depressive symptoms were linked by PHQ2 (feeling down, depressed, or hopeless), GAD6 (becoming easily annoyed or impatient), GAD5 (unable to sit still because of anxiety), GAD7 (feeling afraid that something terrible is about to happen), and PHQ6 (feeling bad or like a failure, or disappointing oneself or family). Conclusions This study identified the central and bridge symptoms in a network of anxiety and depressive symptoms. Targeting these symptoms can contribute to interventions for patients with HF at risk of—or suffering from—anxiety and depressive symptoms, which can be effective in reducing the comorbidity of anxiety and depression.